Undergraduate Students’ Entrepreneurial Attitude and Self-employment Intentions - Kisubi, Moses Kisame (SEISENSE Business Review, 2021)
The study aimed at determining the interactive effect of entrepreneurial attitude and self-efficacy on students’ self-employment intentions. To attain the purpose of the study, cross-sectional and explanatory research designs were employed. Systematic sampling technique was utilized to collect data from a sample of 458 undergraduate finalists from Makerere and Kyambogo Universities in Uganda. Data were analyzed using Hayes (2018) Process macro version 3.2 (Model 1) with the help of SPSS version 23. The study indicates that entrepreneurial attitude and self-efficacy significantly and positively influence self-employment intentions. Further, a negative and significant conditional effect of entrepreneurial self-efficacy in the relationship between entrepreneurial attitude and self-employment intentions was established. Theoretically, the study contributes to the extant literature by providing new insights on the interactive effect of entrepreneurial attitude and self-efficacy on students’ self-employment intentions. We also provide practical implications to educators, curriculum developers, and university management in developing appropriate training tools for students driven by first ascertaining their levels of self-efficacy. The study provides new insights on the conditional effect of entrepreneurial self-efficacy in the relationship between entrepreneurial attitude and self-employment intentions.
Keywords: Entrepreneurship, Entrepreneurial attitude, Entrepreneurial Self-efficacy, Self-employment intentions, Students, Uganda